ANALISIS KESIAPAN SPIN-OFF UNIT USAHA SYARIAH MENJADI BANK UMUM SYARIAH - Ghaida Aulia Purwantika; Mauluddi, Hasbi Assidiki (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
Article 68 Law no.21 of 2008 states that conventional commercial banks with sharia business entities with assets of at least 50% of the parent bank’s or 15 years after the enactment of this law, namely in 2023, are required to separate themselves or become sharia commercial banks. However, most of the sharia business units owned by BPD are not ready to be spin-off. The purpose of this study is to analyze whether UUS BPD is ready to split in 2023 in terms of capital, total assets, and level of solvency. Readiness analysis can be seen from forecasting results based on information published by OJK and the banks concerned. An analysis of the readiness of the BPD UUS spin-off shows that not a single UUS is ready to split in 2023.